2011
DOI: 10.1590/s1808-18512011000400011
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do emprego do GM1 após lesão medular experimental em ratos

Abstract: OBJETIVO: Avaliar a eficácia do GM1, administrado por via intraperitoneal, após lesão medular experimental em ratos. MÉTODOS: Foram utilizados 20 ratos da raça Wistar machos, adultos jovens, com média de idade de 20 semanas, pesando em torno de 350 g, divididos em dois grupos de 10 animais. No grupo 1 foi administrado apenas soro fisiológico por via intraperitoneal. Ao grupo 2, administraram-se 30 mg/kg de GM1 diariamente por essa mesma via. As lesões foram produzidas seguindo-se o protocolo internacional MASC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(29 reference statements)
0
1
0
Order By: Relevance
“… 19 , 20 Although there is no consensus, GM-1 shows with to be a promising therapeutic option, evidence of its benefit both isolated or in combination with other physical, chemical or biological means have been found in the literature. Souza et al, 21 although not statistically significant, demonstrated the benefit of GM-1 in rats with experimental spinal cord injury, reaching higher rank in the assessment by the BBB score.…”
Section: Discussionmentioning
confidence: 92%
“… 19 , 20 Although there is no consensus, GM-1 shows with to be a promising therapeutic option, evidence of its benefit both isolated or in combination with other physical, chemical or biological means have been found in the literature. Souza et al, 21 although not statistically significant, demonstrated the benefit of GM-1 in rats with experimental spinal cord injury, reaching higher rank in the assessment by the BBB score.…”
Section: Discussionmentioning
confidence: 92%